Revision of the European species of Calotelea Westwood (Hymenoptera: Platygastroidea) - Popovici, Ovidiu Alin; Masner, Lubomir; Notton, David G.; Popovici, Mariana (Zootaxa, 2013)
The European species of Calotelea are reviewed: previously known species are redescribed; two new species are de-scribed: Calotelea carbonaria n. sp. and Calotelea laminata n. sp.; and a key to all species is given. Calotelea affinis Ko-zlov & Kononova is a junior synonym of Calotelea elegans (Masi) syn. nov. and Calotelea ruficollis (Szelényi) is transferred to Calliscelio comb. nov. Calotelea laminata n. sp. is the first species of Calotelea belonging to the ocularis group to be recorded from Europe. A morphometric analysis is made of the metasoma of females of all European species of Calotelea.